A methodology for estimating the value of privacy in information disclosure systems. (August 2016) - Hirschprung, Ron; Toch, Eran; Bolton, Frank; Maimon, Oded
Abstract: In many types of information systems, users face an implicit tradeoff between disclosing personal information and receiving benefits, such as discounts by an electronic commerce service that requires users to divulge some personal information. While these benefits are relatively measurable, the value of privacy involved in disclosing the information is much less tangible, making it hard to design and evaluate information systems that manage personal information. Meanwhile, existing methods to assess and measure the value of privacy, such as self-reported questionnaires, are notoriously unrelated of real–world behavior. To overcome this obstacle, we propose a methodology called VOPE (Value of Privacy Estimator), which relies on behavioral economics' Prospect Theory (Kahneman & Tversky, 1979) and valuates people's privacy preferences in information disclosure scenarios. VOPE is based on an iterative and responsive methodology in which users take or leave a transaction that includes a component of information disclosure. To evaluate the method, we conduct an empirical experiment (n = 195), estimating people's privacy valuations in electronic commerce transactions. We report on the convergence of estimations and validate our results by comparing the values to theoretical projections of existing results (Tsai, Egelman, Cranor, & Acquisti, 2011), and to another independent experiment that required participants to rank the sensitivity of information disclosure transactions. Finally, we discuss how information systems designers and regulators can use VOPE to create and to oversee systems that balance privacy and utility. Graphical abstract: Highlights: We propose a methodology (called VOPE) to valuate people's perceptions of privacy. System designers and regulators can use VOPE to balance users' privacy and utility. VOPE applies behavioral economics Prospect Theory in an iterative feedback process. A user study (n = 195) shows that valuations converge with the number of iterations. We validated VOPE by comparing valuations to ranking of privacy choices.